0% found this document useful (0 votes)
25 views

Tutorial 3

The document outlines the topics to be covered in Tutorial 3, including: 1) Proving inferences using rules of inference 2) Converting logical statements to conjunctive normal form (CNF) 3) Using resolution to determine which logical statements are tautologies 4) Converting sentences to clausal form 5) Applying propositional resolution to pairs of clauses 6) Using propositional resolution to show that a set of clauses is not simultaneously satisfiable 7) Using propositional resolution to prove a conclusion from given premises

Uploaded by

Divyanshu Bose
Copyright
© © All Rights Reserved
Available Formats
Download as PDF, TXT or read online on Scribd
0% found this document useful (0 votes)
25 views

Tutorial 3

The document outlines the topics to be covered in Tutorial 3, including: 1) Proving inferences using rules of inference 2) Converting logical statements to conjunctive normal form (CNF) 3) Using resolution to determine which logical statements are tautologies 4) Converting sentences to clausal form 5) Applying propositional resolution to pairs of clauses 6) Using propositional resolution to show that a set of clauses is not simultaneously satisfiable 7) Using propositional resolution to prove a conclusion from given premises

Uploaded by

Divyanshu Bose
Copyright
© © All Rights Reserved
Available Formats
Download as PDF, TXT or read online on Scribd
You are on page 1/ 2

Tutorial 3 Date : 31th August 2020

1. Prove using rules of inference :

2. Convert to CNF

(a) ¬(p ↔ q)
(b) ((p → q) ∧ q) → p
(c) (p ↔ q) ↔ r
(d) p → ( q ↔ r)
(e) (¬p ∧ ( q ↔ p)) → ((q ∧ p) ∨ p)

3. Using the method of resolution check which of the following formulae are tautologies.
(a) ((p → q) → q) → q
(b) ((q → p) → q) → q
(c) ((p → q) ∧ (p → q)) → p
(d) ((p ∨ q) → r) → ( q ∧ r)
(e) ((p → q) ∧ (p → r)) → (p → (q ∧ r))
(f) ((p → r) ∧ (q → r)) → ((p ∧ q) → r)
(g) ((p → r) ∨ (q → r)) → ((p ∨ q) → r)
(h) ((p → r) ∧ (q → r)) → ((p ∨ q) → r)
(i) p → ((q → r) → ((p → q) → r))
(j) (p → (q → r)) → ((p → q) → (p → r))

4.  Convert the following sentences to clausal form.

(a) p ∧ q ⇒ r ∨ s
(b) p ∨ q ⇒ r ∨ s
(c) ¬(p ∨ q ∨ r)
(d) ¬(p ∧ q ∧ r)
(e) p ∧ q ⇔ r

5. What are the results of applying Propositional Resolution to


the following pairs of clauses.

(a) {p, q, ¬r} and {r, s}


(b) {p, q, r} and {r, ¬s, ¬t}
(c) {q, ¬q} and {q, ¬q}
{¬p, q, r} and {p, ¬q,
(d)
¬r}

6.  Use Propositional Resolution to show that the clauses {p, q},


{¬p, r}, {¬p, ¬r}, {p, ¬q} are not simultaneously satisfiable.

7. Given the premises (p ⇒ q) and (r ⇒ s), use Propositional


Resolution to prove the conclusion (p ∨ r ⇒ q ∨ s).

You might also like